Droplet-based microreactor system for stepwise recovery of precious metal ions from real metal waste with calix[4]arene derivatives. Issue 8 (24th May 2018) - Sathuluri, Ramachandra Rao; Kurniawan, Yehezkiel Steven; Kim, Jee Young; Maeki, Masatoshi; Iwasaki, Wataru; Morisada, Shintaro; Kawakita, Hidetaka; Miyazaki, Masaya; Ohto, Keisuke
ABSTRACT: Stepwise recovery of silver(I), palladium(II) and platinum(IV) with suitable calix[4]arene extractants was carried out by investigating the extraction and stripping process using a droplet-based microreactor system. The highest percentages of silver, palladium (100%) and platinum ion (37.2%) were extracted from a real waste only within 4.00s using a microreactor system compared with 24 and 72 h to reach extraction equilibrium in a batch method. Fourier transform infrared spectroscopy studies revealed a very good relation in peak shifts on the metal complexation with calix[4]arene derivatives after extraction and stripping. The droplet-based microreactor system emerges as an effective tool to be applied in metal recovery.